Pendidikan dalam Perspektif Hadis: Syarh Al-Hadis Al-Mawdhu’i - Alamri, Limyah (IAIN Samarinda, 2012)
There are large number of hadis related to education, and they are available in al-kutub al-tis’ah. This article explains hadis about education which classified into five sub themes. They are (1) The eminence of educating children. It is found syarah that educating children has more eminence than charity. (2) Urgency of teaching knowledge through education. It is understood that teaching knowledge to others is very important and compulsory for every moslem. (3) Reward for knowledge seeker in education. It is understood that somebody who seek the knowledge in education is going to have reward to be placed in heaven. (4) Concept of fitrah in the world of education. In this case, fitrah of children has to be developed in the process of Islamic education. (5) Shalat education to children. In this hadis, it can be understood that parents’ obligation is to educate their children to do shalat as early as possible since they are seven years old.